PENGARUH SIKAP TERHADAP PERILAKU, NORMA SUBJEKTIF, DAN KONTROL PERILAKU PERSEPSIAN TERHADAP NIAT MAHASISWA AKUNTANSI UNTUK MENGAMBIL SERTIFIKASI CHARTERED ACCOUNTANT - Duwi Mihartinah; Isma Coryanata (Jurnal Akuntansi, 2018)
This study aims to determine the factors that affect the intention of students to get Chartered Accountant (CA) certification. Using the Theory of Planned Behavior (TPB), the intention of accounting students to take the CA certification related to three variables are attitudes toward behavior, subjective norms, and behavioral control percepsian. Sample in this research is student of accountancy force of 2014 which is in 5 State University (PTN) of South Sumatera (Sumbagsel). Data collection methods in this study used survey methods by distributing questionnaires online through social media. Data analysis techniques using the help of SPSS 23 program. The result of the research shows that attitude factor toward behavior has no effect on accountant's intention to take CA certification, perception behavior control factor negatively affect accounting student's intention to take CA certification. And subjective norms factor positively affect the intention of accounting students to take the CA certification.Key words: TPB, intention, accountant, subjective norm, control